Cyclopropylamine plasma polymers for increased cell adhesion and growth. Issue 7 (11th November 2016) - Manakhov, Anton; Landová, Marie; Medalová, Jiřina; Michlíček, Miroslav; Polčák, Josef; Nečas, David; Zajíčková, Lenka
Abstract : Plasma polymers with NHx groups were deposited from cyclopropylamine in low pressure radio frequency (RF) discharges. The amount of NHx decreased with increasing average power P av, whereas the layer dissolution in water decreased and high P av led to a slight film swelling. The C2C12 cells demonstrated very high adhesion to the layers regardless of the deposition conditions. Although the surface chemistry of amine‐rich layers should enhance the cell proliferation, the WST‐1 assay, and immunocytochemistry revealed lower cell proliferation and viability on the layers exhibiting above 18% of relative thickness loss in water. Promising results were obtained on the layers with better water stability and bearing 7–10% of NHx . Abstract : By tuning the average plasma power it is possible to prepare cyclopropylamine layers with different content of amine groups and various water stability. The C2C12 cells demonstrated a very high adhesion to the plasma polymerized layers regardless of the deposition conditions. Nevertheless, the WST‐1 assay and immunocytochemistry revealed lower cell proliferation and viability on layers exhibiting poor stability in water even in comparison with uncoated surfaces.